G506(P) Exploring bronchopulmonary dysplasia (bpd) rates in preterm infants: an in-depth analysis. (May 2019) - Fuller, MA; Slater, C; Ponnusamy, V
Abstract : Background: UK National Neonatal Audit Programme (NNAP) 2017 defines BPD by level of respiratory support at 28 days and 36 weeks corrected age. Based on this, UK national incidence of BPD for Level 3 NICU's remain around 40%. We aimed to review our data, including radiological evidence to define BPD rate accurately to improve our practice. Method: Included neonates born between January to December 2016, under 32 weeks gestation and admitted to our NICU. Excluded those who died or transferred for special care/surgery. Data collected through BadgerNet and medical records, and subgroup analysis done for inborn and out-born babies. Results: Despite predominant non-invasive ventilation in our unit, 50/105 (47.6%) neonates had BDP according to NNAP definition. Demographics showed median birth gestation 28+3 weeks, median birthweight 1041 g, median days of invasive ventilation – 3, BiPAP- 3, CPAP – 6, nasal High flow −18 and nasal oxygen – 22. Additionally, 95% received at least one dose of antenatal steroids, 33% had PROM, 61% received surfactant, median dose 200 mg/kg and median age of 1 hour, and 22% received postnatal steroids, predominantly inhaled budesonide. Of 50 neonates with BPD, 38 did not have a chest X-ray around 36 weeks as not clinically indicated; 7 had normal chest X-ray; and 2 had signs of consolidation. Only 3 (6%) had radiological evidence of BPD. While the overall rate of 47.6% is higher than UK national average for level 3 NICU's, this does not reflect true rate of BDP. Babies with other pathologies like cardiac, gastro-oesophageal reflux and pneumonias were also included within NNAP definition. The rate of BPD also varies between inborn and out-born babies based on units' practice. Additionally, rate of BPD also falls slightly to 37% at term corrected age. Conclusion: Our rates of BPD appear high despite non-invasive ventilation. Review of definition to capture accurate data is vital to identify true BPD rate in every unit. This will help to improve practices around management of BPD in at risk infants, including early use of surfactant and improved nutrition. Using 40 weeks cut off might be more clinically relevant for long term respiratory morbidities.